2(113-2c)+4c=226

Simple and best practice solution for 2(113-2c)+4c=226 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(113-2c)+4c=226 equation:


Simplifying
2(113 + -2c) + 4c = 226
(113 * 2 + -2c * 2) + 4c = 226
(226 + -4c) + 4c = 226

Combine like terms: -4c + 4c = 0
226 + 0 = 226
226 = 226

Add '-226' to each side of the equation.
226 + -226 = 226 + -226

Combine like terms: 226 + -226 = 0
0 = 226 + -226

Combine like terms: 226 + -226 = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 20+10x-(8x-12)=68 | | .03x+.07(18000-x)=90 | | 4k-(-6)=-2-(-16)-(-2) | | 6n-.7=11 | | 10+n=25 | | -18x^2+51x+8=0 | | X^2+6x+64=48 | | 9x^4-64=0 | | 4c^2+7x-15=0 | | 15+n=6 | | 3x^4-7x^2=0 | | (4x+2)-x=(2x-10) | | 9(2+v)+35v=14v | | .5x(x+4)=16 | | 69=12 | | 2a+4b=226 | | 8(4+v)+34v=14v | | -2.3q+16=-5q-3 | | x^2+6x-24.01=0 | | 10*x+4=12*x-16 | | 3+2(x-1)=4x | | 3+2n-6=25 | | 8z+11=7z+5 | | 4(12n-6)=6(-4+5n)+18n | | 2x-2.8-2.4x+2.6x-5= | | 6(-3-x)-2*x=14 | | 6sec^2(0)-2sec^2(0)= | | 4x^4+21x^2-18=0 | | -7=7-(8-a) | | Y=50+1x | | yz^2-z^2+5+3yz-3z^2+4yz= | | 16=7-(b+9) |

Equations solver categories